PENELITIAN ARKEOLOGI YANG IMPLEMENTATIF “SATU OBSESI HASIL PENELITIAN ARKEOLOGI MASA DEPAN” - Gunadi Kasnowihardjo (Balai Arkeologi Provinsi Sulawesi Selatan, 2009)
Why the system of archaeological resource management, archaeological research sector still feel marginalized? The question is this controversial writer intentionally throwing at the beginning of this essay to discourse can arouse the attention of the honorable readers. There are two dominant factors affecting the occurrence of disharmony in the archaeological resource management system in Indonesia. Both these factors are internal factors, namely errors in determining the strategy and work program of archaeological research. Thus far the research results are always the conclusion that the research should be continued for the future or the next financial year (never ending research). Apart from that research results in the form of archaeological research reports are stopped at the library. Recapitulation of the results of research reports in the three Branch of Archaeological Research Centre Such as Balai Arkeologi Yogyakarta, Banjarmasin, and Makassar, almost all of the results of archaeological research for a decade (1994 - 2004) not able to enter the